THE EFFECT OF TEACHER COMPETENCY ON THE QUALITY OF THE LEARNING PROCESS AT TK ABA GUNUNGSITOLI - Syifaushudur Harefa; Selamat Pohan (Proceeding International Seminar of Islamic Studies, 2022)
Teacher competence is one of the benchmarks for the success of the education implemented. Therefore, qualified educators will be able to produce students who grow according to their stage of development. This study aims to determine how much influence the competence of the teacher has on the effectiveness of the learning process. The competencies in question include: Pedagogic, Professional, and Social Competencies. This study uses a qualitative descriptive type of research to explore the excavations owned by PAUD teachers at the Private Kindergarten 'Aisyiyah Bustanul Athfal Gunungsitoli through the methods of conversing, interviewing, and asking questions and paying attention to the learning process every day which is carried out at Tk 'Asiyiyah Bustanul Athfal . The results of the study show that the competence of the teacher greatly influences the learning process, this then has an impact on the low learning process, because it cannot stimulate children's development optimally, the media is not varied and the method is not in accordance with the characteristics of the child. In addition, teachers' understanding of learning design is still minimal which causes the learning process to be less interesting.